Metasomatized mantle under the Eastern Mexican Alkaline Province: evidence from the Oligocene Rincón Murillo Gabbro, Sierra de San Carlos-Cruillas, NE México - Victor Alejandro Leal-Cuellar; Juan Alonso Ramírez-Fernández; Reneé González-Guzmán; Fernando Velasco-Tapia; Luigi Solari; Luis Alejandro Elizondo-Pacheco; Juan Carlos Montalvo-Arrieta; José Jovany Rivera-García; Bodo Weber (International Geology Review, 2024)

Magmatic source, petrogenesis, and tectonic setting of the Concepción del Oro Igneous Complex: a geochemical and isotopic (Rb–Sr and Sm–Nd) study of a late complex of the Cretaceous–Eocene Mexican Magmatic Arc - Reneé González-Guzmán; Fernando Velasco-Tapia; Bodo Weber; Peter Schaaf; Rogelio Sosa-Valdés; Luigi Solari (International Journal of Earth Sciences, 2023)
During the Mexican fold-and-thrust belt tectonics, the inboard migration of long-term cordilleran magmatism typifies the geological setting during the Cretaceous–Paleogene period. The Concepción del Oro Igneous Complex (COIC) represents one of the most internal and isolated magmatic pulses that occurred during this magmatic activity. In this work, plutonic rocks from the COIC were studied using petrography, U–Pb geochronology, whole rock and zircon geochemistry, and Rb–Sr and Sm–Nd isotopes. Petrographic observations reveal mainly fine-to-coarse-grained granodioritic composition for most plutonic masses. U–Pb zircon analyzes of four samples from the largest plutonic center of the COIC yielded ages ranging from 42.6 ± 0.2 Ma to 41.8 ± 0.1 Ma. The granodiorites exhibit geochemical features typical of I-type, high-K calc-alkaline, Magnesian rocks. The chondrite-normalized REE diagram summarizes enrichment of LREE ([La/Yb] N = 5.94–19.19) and moderate to slightly negative Eu anomalies (Eu/Eu* = 0.63–0.94). In addition, the mantle-normalized spider diagram shows enrichment of LILE, such as Rb and Ba, and depletion of HFSE, such as Nb, Ta, Ti, and P. Whole-rock and zircon geochemistry indicate a post-collisional setting with an inherited magmatic arc fingerprint. Ti-in-zircon temperatures and zircon saturation thermometry suggest a magmatic origin from evolved and relatively cold melts (~ 700 °C). Moreover, the systematic variations in the ratios of highly incompatible elements, such as La/Sm (6.54–3.79) and Rb/Sr (0.32–0.10), and relatively narrow ranges in Zr/Hf (36.25–48.84) and 147 Sm/ 144 Nd (0.0941–0.1261), suggest fractional crystallization as the main petrogenetic process involved in the formation of the COIC rocks. Whole-rock isotopic data suggest a magma source mixing juvenile material with older continental crust, as indicated by 87 Sr/ 86 Sr ( t = 40) ratios between 0.704583 and 0.707783, 143 Nd/ 144 Nd ( t = 40) ratios varying in the ranges of 0.512478–0.512702 (εNd ( t = 40) = from + 2.18 to − 2.10), and TDM (Nd) ranging from 1.03 to 0.62 Ga. We conclude that the parental source of the COIC was derived from partial melting of the lower crust triggered by emplacement of an underplated magma at the base of the crust during the end of an orogenic cycle.

The Sierra de Juárez Complex: a new Gondwanan Neoproterozoic-early Palaeozoic metamorphic terrane in southern Mexico - Guillermo Espejo-Bautista; Fernando Ortega-Gutiérrez; Luigi A. Solari; Roberto Maldonado; Yuly T. Valencia-Morales (International Geology Review, 2022)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Transportability of confined field trial data for environmental risk assessment of genetically engineered plants: a conceptual framework - Monica Garcia-Alonso; Paul Hendley; Franz Bigler; Edgar Mayeregger; Ronald Parker; Clara Rubinstein; Emilio Satorre; Fernando Solari; Morven A. McLean (Transgenic Research, 2014)

Detrital provenance of the Grenvillian Oaxacan Complex, southern Mexico: a zircon perspective - Luigi A. Solari; Fernando Ortega-Gutiérrez; Mariano Elías-Herrera; Carlos Ortega-Obregón; Consuelo Macías-Romo; Margarita Reyes-Salas (International Journal of Earth Sciences, 2014)

Petrology of high-grade crustal xenoliths in the Chalcatzingo Miocene subvolcanic field, southern Mexico: buried basement of the Guerrero-Morelos platform and tectonostratigraphic implications - Fernando Ortega-Gutiérrez; Mariano Elías-Herrera; Arturo Gómez-Tuena; Laura Mori; Margarita Reyes-Salas; Consuelo Macías-Romo; Luigi A. Solari (International Geology Review, 2012)